2020
DOI: 10.1155/2020/8026838
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Imperatorin on Acetaminophen Overdose-Induced Acute Liver Injury

Abstract: Acetaminophen (APAP) toxicity leads to severe acute liver injury (ALI) by inducing excessive oxidative stress, inflammatory response, and hepatocyte apoptosis. Imperatorin (IMP) is a furanocoumarin from Angelica dahurica, which has antioxidant and anti-inflammatory effects. However, its potential to ameliorate ALI is unknown. In this study, APAP-treated genetic knockout of Farnesoid X receptor (FXR) and Sirtuin 1 (SIRT1) mice were used for research. The results revealed that IMP could improve the severity of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
(50 reference statements)
1
25
0
Order By: Relevance
“…In particular, palmitic acid that could lead to insulin resistance by binding directly with MD2 to activate TLR4/NF-κB signal pathway [ 29 ]. Meanwhile, several potential metabolites which possess anti-inflammatory and anti-oxidation stress activities were reduced in cisplatin compared to control group [ 31 35 ]. It is reported that imperatorin could attenuate dextran sulphate sodium induced colitis by targeting pregnane X receptor to inhibit inflammatory response in mice [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, palmitic acid that could lead to insulin resistance by binding directly with MD2 to activate TLR4/NF-κB signal pathway [ 29 ]. Meanwhile, several potential metabolites which possess anti-inflammatory and anti-oxidation stress activities were reduced in cisplatin compared to control group [ 31 35 ]. It is reported that imperatorin could attenuate dextran sulphate sodium induced colitis by targeting pregnane X receptor to inhibit inflammatory response in mice [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that imperatorin could attenuate dextran sulphate sodium induced colitis by targeting pregnane X receptor to inhibit inflammatory response in mice [ 34 ]. In addition, prominent research efforts have elaborated that imperatorin could protect against drug induced liver injury associated with decrease level of inflammation cytokines and oxidative stress in mice [ 35 ]. We mapped metabolites to physiological pathways and observed significant differences in the levels of several pathways responsible for metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, long term administration or overdoses of APAP can cause a deleterious effect on the liver [ 6 ]. APAP-induced liver injury was well recognized by numerous studies- [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…Celastrol has a protective effect on cholestatic liver injury by regulating SIRT1/FXR pathway (Zhao et al, 2019). Other research revealed that imperatorin exerts the protective effect against hepatotoxicity induced by excessive acetaminophen similarly by stimulating the SIRT1/FXR pathway (Gao et al, 2020). Moreover, studies have showed that NAFLD may be mitigated through the regulation of SIRT1/FXR signaling pathway (Han et al, 2019).…”
Section: Discussionmentioning
confidence: 99%